DEVELOPING STUDENTS’ CREATIVE AND PROFESSIONAL COMPETENCIES IN VISUAL ARTS: EFFECTIVE PEDAGOGICAL AND PSYCHOLOGICAL STRATEGIES - Eshmatov Samariddin Hamza oʻgʻli, (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines pedagogical and psychological strategies aimed at developing students’ creative and professional competencies in visual arts lessons. It highlights the role of interactive teaching methods, project-based learning, individualized approaches, and motivational techniques in fostering students’ artistic skills and professional growth. The study emphasizes the importance of a supportive classroom environment and flexible teaching methods to enhance students’ engagement, creativity, and professional competence.